Bobby Cochran - Willamette Partnership - Cochran, Bobby, speaker (Colorado State University. Libraries, 2011)
In Panel discussion #1, representatives from three stakeholders of an ecosystem marketplace discuss the creation of the market, how their organizations participate, and why they are participating. Participants include a farmer (supply side), water utility (demand side), and market organizer.

In this video, Bobby Cochran, a market organizer from Willamette Partnership, speaks as a representative of one of three stakeholders of an ecosystem marketplace.
Functioning ecosystem marketplace - Willamette partnership
Presented at a workshop entitled "Stepping toward the future: marketing environmental services on working lands of the American West" on May 23-25, 2011 on the CSU campus. The purpose of the workshop was to bring together regional and national leaders from the ranching community, conservation organizations, businesses, universities, and government to explore ways to catalyze the development of payments for ecosystem services in Colorado and across the American West. Over 80 participants attended the conference, which also highlighted the CCC's work to create an ecosystem marketplace in northern Colorado.
Includes recorded video presentation.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: stakeholders; ecosystem services; environmental markets